Two new Gammarus species and a new name (Crustacea: Amphipoda: Gammaridae) from Northwest China - Zhao, Shuangyan; Meng, Kaibaryer; Hou, Zhonge (Zootaxa, 2017)
Two new species of the genus Gammarus are described and illustrated from Northwest China. A new species name Gammarus tianshan nom. nov. is proposed to replace G. montanus Hou et al., 2004. Gammarus simplex sp. nov. from Altay, Xinjiang, is characterized by uropod III with simple setae on both rami and urosomite I only with setae on dorsal margin. Gammarus glaber sp. nov. from Qinghai, is characterized by uropod III with few simple and plumose setae. Detailed morphological description and differences from related species are discussed. A distribution map of the new species and related species is provided.